Insights into the structure–activity relationship of a type III secretion system inhibitor, aurodox. (1st August 2022) - Kimishima, Aoi; Hagimoto, Daichi; Honsho, Masako; Watanabe, Yoshihiro; Iwatsuki, Masato; Tsutsumi, Hayama; Inahashi, Yuki; Naher, Kamrun; Sakai, Kazunari; Kuwae, Asaomi; Abe, Akio; Asami, Yukihiro
Graphical abstract: Abstract: Aurodox was originally isolated in 1972 as a linear polyketide compound exhibiting antibacterial activity against Gram-positive bacteria. We have since identified aurodox as a specific inhibitor of the bacterial type III secretion system (T3SS) using our original screening system for inhibition of T3SS-mediated hemolysis in enteropathogenic Escherichia coli (EPEC). In this research, we synthesized 15 derivatives of aurodox and evaluated EPEC T3SS inhibitory activity as well as antibacterial activity against EPEC. One of the derivatives was highly selective for T3SS inhibition, equivalent to that of aurodox, but without exhibiting antibacterial activity (69-fold selectivity). This work revealed the structure–activity relationship for the inhibition of T3SS by aurodox and suggests that the target of T3SS is distinct from the target for antibacterial activity.